Helicobacter pylori Eradication Rate in Patients with Diabetes - Jiyeon Yoo; Yeong Ji Yu; Gumin Cho; Hongkwon Oh; Seung Hyun Oh; Tae Ho Kim; Jung Hwan Oh (Yong Chan Lee, 2017)
Background/Aims: The prevalence of diabetes mellitus is increasing. Little is known about the difference in Helicobacter pylori eradication rates between diabetic patients and non-diabetics. The aim of this study was to compare the eradication rate between diabetic and non-diabetic patients. Materials and Methods: The medical records of patients who received a proton pump inhibitor (PPI)-based eradication therapy between 2012 and 2015 were retrospectively reviewed. All the patients underwent endoscopic biopsy to confirm H. pylori infection. Successful eradication was confirmed by using the 13C-urea breath test, biopsy, or rapid urease test, which was performed at least 4 weeks after the end of eradication therapy. Results: A total of 1,402 patients were included. The eradication rate was 74.3% (1,041/1,402; 95% CI, 72.0∼76.5%). Excluding 151 patients who were confirmed to have no diabetes, 182 diabetic and 1,069 non-diabetic patients were compared. No significant difference (P=0.667) in eradication rate with PPI-amoxicillin-clarithromycin therapy was found between the diabetic (75.8%, 138/182; 95% CI, 69.6∼82.0%) and non-diabetic groups (74.0%, 791/1,069; 95% CI, 71.4∼76.6%). Peptic ulcer was much more common in the diabetic group than in the non-diabetic group (67.0% vs. 57.9%, P=0.038). Conclusions: The H. pylori eradication rate with PPI-based triple therapy in the diabetic patients was probably not different from that in non-diabetic patients.